2016
DOI: 10.2119/molmed.2015.00176
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Anti-HMGB1 Monoclonal Antibody Does Not Affect Lupus Nephritis in MRL/lpr Mice

Abstract: High mobility group box 1 (HMGB1) is a nuclear DNA binding protein that acts as an alarmin when secreted. HMGB1 is increased in systemic lupus erythematosus and might represent a potential therapeutic target. We investigated whether treatment with an anti-HMGB1 antibody affects the development of lupus nephritis in MRL/lpr mice. Seven-week-old MRL/lpr mice were injected intraperitoneally twice weekly for 10 wks with 50 μg monoclonal anti-HMGB1 (2G7, mouse IgG2b) (n = 12) or control antibody (n = 11). Control M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
0
17
1
1
Order By: Relevance
“…Moreover, we first tried subcutaneous injection using the same dosage (5 mg/kg) as a preliminary experiment; however, we were not able to find any beneficial effects for MRL/ lpr mice ( data not shown ). Although our results could not show absolute efficacy (organomegaly and serological abnormalities did not improve), increased dose and higher blood concentration compared to the previous study might contribute to the efficacy for nephritis 18 . However, HMGB1 was actively translocated from the nucleus in MRL/ lpr mice, as determined by immunofluorescence; therefore, the dose might be insufficient to antagonize the target in this mouse model.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Moreover, we first tried subcutaneous injection using the same dosage (5 mg/kg) as a preliminary experiment; however, we were not able to find any beneficial effects for MRL/ lpr mice ( data not shown ). Although our results could not show absolute efficacy (organomegaly and serological abnormalities did not improve), increased dose and higher blood concentration compared to the previous study might contribute to the efficacy for nephritis 18 . However, HMGB1 was actively translocated from the nucleus in MRL/ lpr mice, as determined by immunofluorescence; therefore, the dose might be insufficient to antagonize the target in this mouse model.…”
Section: Discussioncontrasting
confidence: 79%
“…Although the antibody dose seems considerably low, they showed attenuated proteinuria, glomerulonephritis, anti-dsDNA, and serum cytokine levels. However, a recent study has reported that the anti-HMGB1 antibody did not affect lupus activities in MRL/ lpr mice 18 . Although this previous study used the same mouse model, the treatment protocol was different from our protocol, i.e., an antibody dose of 100 μg/mouse/week was used in contrast to our dose of approximately 150–400 μg/mouse/week, with peritoneal administration and a treatment period of 7–17 weeks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Administration of monoclonal anti-HMGB1 antibodies have shown opposing effects in animal models of lupus [83,84]. In animal models of arthritis anti-HMGB1 treatment have attenuated the disease [85,86].…”
Section: Antibodies Against High Mobility Group Box Protein-1 (Hmgb1)mentioning
confidence: 99%
“…Studies in animal models of arthritis have shown that treatment with anti-HMGB1 antibodies can attenuate disease by blocking pro-inflammatory actions of HMGB1 [85,86]. Opposing effects of anti-HMGB1 have been demonstrated in two different murine lupus models [83,84]. HMGB1 has different…”
Section: Antibodies Against High Mobility Group Box Protein-1 (Hmgb1)mentioning
confidence: 99%